Authentication of Italian PDO lard using NIR spectroscopy, volatile profile and fatty acid composition combined with chemometrics. (1st December 2016) - Chiesa, L.; Panseri, S.; Bonacci, S.; Procopio, A.; Zecconi, A.; Arioli, F.; Cuevas, F.J.; Moreno-Rojas, J.M.
Highlights: Food authenticity are of great concern to consumers seeking high quality products. Confirmation of authenticity of meat products like PDO lard remain an emerging topic. A non-destructive and fast technique was used performing models with excellent results. NIR model combined with fatty acids and volatile compounds was able to authenticate PDO lard. Abstract: This study analysed the usefulness of near infrared spectroscopy (NIRS), combined with volatile compound (VOC) and fatty acid (FA) analyses, for the authentication of the unique Italian Valle d'Aosta Arnad Protected Designation of Origin (PDO) lard. Ensuring the authenticity of high value meat products remains an emerging topic within the food sector. This study validated a FA, VOC and NIRS model for use in the authentication of Arnad PDO lard. The model showed a high potential rate to recognize patterns in lard samples. In particular the sensitivity and specificity calibration values were both 100%, and cross-validation models were performed using FAs and VOCs separately. The NIRS model obtained sensitivity and specificity values of 98.2% in the calibration data set, and 94.4% in the cross-validation step. This analytical approach may represent an effective tool to prevent food fraud, which is crucial for meat derived products with a high commercial value.